2016
DOI: 10.1515/pomr-2016-0048
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Configurations of Wave Energy Converter Arrays with a Floating Body

Abstract: An array of floating point-absorbing wave energy converters (WECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The focus of this review is work that has attempted to optimise array design either by parametric study or optimisation algorithms. A small array of four point absorbers connected to a moored disk has been optimized as a function of incident wave direction, separating distance between the absorbers and the PTO damping using a BEM approach (Zhang et al, 2016). All these factors have a great influence in the power absorption and have influence between each other.…”
Section: (Single Column Image)mentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of this review is work that has attempted to optimise array design either by parametric study or optimisation algorithms. A small array of four point absorbers connected to a moored disk has been optimized as a function of incident wave direction, separating distance between the absorbers and the PTO damping using a BEM approach (Zhang et al, 2016). All these factors have a great influence in the power absorption and have influence between each other.…”
Section: (Single Column Image)mentioning
confidence: 99%
“…Most of the research currently available is related to point absorbers and Oscillating Wave Surge Converters (Child, 2011;Sarkar, Renzi and Dias, 2014;Zhang et al, 2016). Oscillating Wave Surge Converters are a shallow water flap type device that operate as a terminator for the waves and consequently devices positioned towards the front of the WEC farm generally have a better performance than the ones at the back (Sarkar, Renzi and Dias, 2014).…”
Section: (Single Column Image)mentioning
confidence: 99%
“…Finally, the optimal layout of the WECs shows different conclusions between different research. [15] has shown that a square configuration of 4 heave floating-point absorbers is better in terms of power production and less sensitive to the wave direction compared with rhombus and triangular configurations. On the other hand, triangular WEC arrays with 9e25 devices whose position is defined by 2 parameters (dx,dy) are preferred in Ref.…”
Section: Introductionmentioning
confidence: 99%